Predication Strategies in Op-Ed Discourse: An Analysis within the Framework of Discourse-Historical Approach - Derya AYDIN; Gülsüm Songül ERCAN (Dilbilim Araştırmaları Dergisi, 2022)
Op-ed writers reflect the ideology of their media organizations in their columns using various linguistic strategies. These strategies can be manifested using the analytic tools provided by Critical Discourse Analysis (CDA). The aim of this study is to analyze how the portrait of Mehmed II painted by the Italian artist Bellini being purchased by Istanbul Metropolitan Municipality on 25 June 2020 is reflected in two op-ed articles in the Sözcü and Yeni Akit newspapers which represent contrasting ideologies. The op-ed articles have been analyzed using the Predication strategy within the framework of Discourse-Historical Approach (Reisigl & Wodak, 2009). Our findings have revealed that predication strategy has been used in the op-ed article in Yeni Akit newspaper to present the opposition between us and them, while it has been used in the op-ed article in Sözcü to create a similarity between the social actors with different ideological orientations by mitigating the distinction between us and them. It has been concluded that the topic at hand is the determining factor for the op-ed writers in conveying their ideologies in the text and that the predication strategy is mainly used to persuade the target audience.